PENGARUH MANAJEMEN LIKUIDITAS TERHADAP KINERJA BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) DI INDONESIA - DEKY ANWAR DEKY (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2016)
This study aims to determine whether there is influence liquidity management on the performance of the People's Financing Islamic Bank in Indonesia. Then determine how liquidity management influence on the performance of the People's Financing Islamic Bank in Indonesia. Variables used in this research consists of Capital Adequacy Ratio (CAR), which is a representation of liquidity Financing Islamic Bank in Indonesia and variable Return on Equity (ROE) as a representation of the performance of Financing Islamic Bank in Indonesia in the period of time during the 31 months from January 2014 to July 2016 , The results obtained indicate that there is significant influence and positive liquidity management on the performance of Financing Islamic Bank in Indonesia. This means that if there is an increase in liquidity will berpengaruah to increased performance of SRB in Indonesia. The amount of liquidity management influence on performance is 0.93%, meaning that when Financing Islamic Bank liquidity rose by 1%, it will affect the performance of Financing Islamic Bank rising 0.93%. The results obtained indicate that there is significant influence and positive liquidity management on the performance of Financing Islamic Bank in Indonesia. This means that if there is an increase in liquidity will berpengaruah to increased performance of SRB in Indonesia. The amount of liquidity management influence on performance is 0.93%, meaning that when Financing Islamic Bank liquidity rose by 1%, it will affect the performance of Financing Islamic Bank rising 0.93%.Kata kunci : liquidity, performance, BPRS.